Achieving sustainability transitions in residential energy use across Europe: The importance of problem framings. (October 2019) - Jensen, Charlotte Louise; Goggins, Gary; Røpke, Inge; Fahy, Frances
Abstract: Reducing greenhouse gas emissions in the residential sector is central to European energy policy. However, the speed and scale of sustainable energy transitions need to accelerate. There is a growing consensus that meeting energy targets is highly dependent on interrelated socio-material and cultural aspects of energy use. New ways of framing energy demand that go beyond dominant efficiency- and behavior models are needed. Recognizing these concerns, this paper reports on a review of 1067 Sustainable Energy Consumption Initiatives (SECIs) that aim to reduce residential energy use across 30 European countries. The initiatives are categorized and a corresponding Problem Framing Typology (PFT) is developed, highlighting important aspects of different types of problem framings. The typology contains four categories including 1) Changes in technology; 2) Changes in individual behavior; 3) Changes in everyday life situations; 4) and Changes in complex interactions. Applying the PFT to the 1067 SECIs shows that the vast majority (75%) of SECIs are positioned within category 1 and 2, indicating a lingering bias towards technocratic consumer behavioral strategies. The limitations of such approaches are discussed, and it is argued that systematically addressing interactions between technology, businesses, culture and everyday-life is more likely to lead to long-term transformation. Highlights: This research mapped 1067 sustainable energy initiatives in 30 countries in Europe. Introducing an innovative framing typology we find that <25% of the SECIs challenge why energy is used. There is an overreliance on behavioral and technological change mechanisms. The paper identifies a need for coherent evaluation schemes for energy use initiatives. We can learn from initiatives that target energy use across sectors and practices.